Developing a deferred maintenance model for public university in Malaysia - Yasin, Mohd. Norazam (2020)
Deferred maintenance has been regarded as a critical issue in maintenance management and has created negative impacts toward the performance of buildings and organization. This issue has become worldwide especially in most developing countries including Malaysia. If this issue is not resolved, the stakeholders may suffer from possible risks of poor organization performance. Similarly, deferred maintenance has also become a pressing issue and has adverse affected the management of public universities in Malaysia. Hence this study is intended to investigate the relationship between causes and effects of deferred maintenance and subsequently, a structural model is developed specifically for public universities in Malaysia. In order to achieve the aim, preliminary expert interviews, questionnaire survey and Partial Least Squares Structural Equation Modelling (PLS-SEM) had been carried out. A total of 220 sets of questionnaires has returned and has been analysed using Statistical Package for Social Science (SPSS) version 22 and Smart PLS-SEM version 3.0 software for modelling the causes and effects relationship. The outcome of the model proved that seven (7) hypotheses found to be positively related. This model consists of 21 deferred maintenance indicators of causes that categorized into 3 groups. The group of causes are “Organization” with 12 indicators, “Resources” with 5 indicators and “Financial” with 4 indicators. The study also identified 23 indicators of effects which are categorized into 4 groups. The groups of effects are “Social” with 8 indicators, “Environment” with 7 indicators, “Technical” with 5 indicators and “Economic” with 3 indicators. The developed model provides useful information and better knowledge to the maintenance of organization and is vital to curb the deferred maintenance problem. It also gives an in depth understanding towards deferred maintenance by explaining the impact load of each indicator involved. The model has also fulfilled the need to visualize the causes and effects of deferred maintenance in a holistic manner. The validation of the model by 14 experts was undertaken to determine its appropriateness and relevancy in enhancing the knowledge and understanding of the relationship. In conclusion, this study has successfully modelled the relationship between the causes and effects of deferred maintenance of public university buildings in Malaysia.